Segurança do paciente: estratégias de enfermagem para prevenção de erros na administração de medicamentos - Marcos Leal Rodrigues Pereira; Gerson Luiz Pereira Emerim da Silva; João Lucas Vaz Macedo; Leandro Ghilardi (Revista ft, 2026)
This study aimed to analyze the nursing strategies used to prevent medication administration errors and promote patient safety. This is an integrative literature review conducted in the SciELO, LILACS, MEDLINE/PubMed, BDENF, and DOAJ databases, considering publications from January 2020 to July 2026 in Portuguese, English, and Spanish. The initial search identified 18 studies, of which 8 comprised the final sample after application of the inclusion and exclusion criteria. The main strategies identified included continuing education, double-checking, application of the rights of medication administration, use of protocols and checklists, correct identification of patients and medications, use of safety technologies, reduction of interruptions and distractions, interprofessional communication, team supervision, and strengthening of the safety culture. The findings indicate that error prevention requires a systemic and integrated approach and does not depend exclusively on the individual attention of healthcare professionals. It is concluded that nursing plays a fundamental role in establishing safety barriers; however, professional practice must be supported by continuous training, adequate work organization, institutional protocols, technologies, and a safety culture focused on prevention and learning from incidents.